Α-LiMB9O15 (M = Sr, Pb): flexible [B3O7] units leading to the low temperature phase of β-LiMB9O15 (M = Sr, Pb). Issue 20 (7th September 2022) - Liu, Kaitong; Han, Jian; Li, Fuming; Han, Shujuan; Yang, Zhihua; Wang, Xuping; Pan, Shilie
Abstract : Under the regulation of a metal cation with a large radius, borates formed from [B3 O7 ] groups have high structural flexibility, and the low-temperature phases of α-LiSrB9 O15 and α-LiPbB9 O15 were obtained. Abstract : Polymorphism is a very important phenomenon in borates and is helpful when studying their structure and properties. Low-temperature phase α-LiMB9 O15 (M = Sr, Pb), crystallized in the chiral space groups P 21 21 21 and P 63, was synthesized via a high-temperature solid reaction, while high-temperature phase β-LiMB9 O15 (M = Sr, Pb) crystallizes in a non-centrosymmetric space group R 3 c . All of these four phases have three-dimensional structures made up of fundamental building units [B3 O7 ] with six-membered rings, yet the [B3 O7 ] units construct B–O frameworks with different types of three-dimensional channels. The TG-DSC measurements and X-ray diffraction of powders at different temperatures show that α-LiSrB9 O15 transforms into β-LiSrB9 O15 at 840 °C, and the high-temperature β-phase compound is a congruent melting compound.